Influences of dietary niche expansion and Pliocene environmental changes on the origins of stone tool making - (:unkn) unknown (My University, 2020)
The world's oldest known stone tools discovered at the Pliocene site of Lomekwi 3 (LOM3) in the Nachukui Formation, northern Kenya, signals a prodigious behavioral change in the hominin lineage. LOM3, dated to 3.3 Ma, is significantly earlier than the first appearance of genus Homo and coincides with the onset of the Mid-Pliocene Warm Period, warranting new phylogenetic and environmental explanations for the origins of hominin stone tool making behaviors. Here we examined Pliocene paleoenvironments (4.3–3.0 Ma) within the Omo-Turkana Depression (OTD) with paleosol pedogenic carbonate (PC) and faunal enamel carbonate (EC) δ13C and δ18O values. Amidst the gradual shift toward grassier environments, intranodular δ13CPC and δ18OPC variation slightly increased through time. Three of fourteen ungulate herbivore taxa yielded statistically significant increases in δ13CEC values. When all ungulate herbivore δ13CEC values are grouped by feeding categories (C3-browsers, C3-C4-mixed feeders, C4-grazers) there is evidence that the C3-C4-mixed feeding niche contracted and shifted toward the C4-grazing niche as hominins expanded their dietary breadth during the middle Pliocene. Only one of nine taxa showed a significant decrease in δ18OEC values across the study interval. Abrupt, significant environmental perturbations are not evident during LOM3 times in the OTD, casting doubt on variability selection or pulsed humidity as selective forces for middle Pliocene technological innovations. We propose that a long-term feedback system involving gradual environmental changes and biotic dietary competition influenced a suite of hominin adaptations to a broad dietary niche, culminating in the origins of stone tool making behaviors.
Keywords: African Research